Analyst Forecast Revisions and Market Price Discovery - Gleason, Cristi A.; Lee, Charles M. C. (The Accounting Review, 2003)
We document several factors that help explain cross-sectional variations in the post-revision price drift associated with analyst forecast revisions. First, the market does not make a sufficient distinction between revisions that provide new information (“high-innovation” revisions) and revisions that merely move toward the consensus (“low-innovation” revisions). Second, the price adjustment process is faster and more complete for “celebrity” analysts (Institutional Investor All-Stars) than for more obscure yet highly accurate analysts (Wall Street Journal Earnings-Estimators). Third, controlling for other factors, the price adjustment process is faster and more complete for firms with greater analyst coverage. Finally, a substantial portion of the delayed price adjustment occurs around subsequent earnings-announcement and forecast-revision dates. Collectively, these findings show that more subtle aspects of an earnings revision signal can hinder the efficacy of market price discovery, particularly in firms with relatively low analyst coverage, and that subsequent earnings-related news events serve as catalysts in the price discovery process.